Movement of St. Louis encephalitis virus in the Western United States, 2014- 2018 - Swetnam, Daniele M.; Stuart, Jackson B.; Young, Katherine; Maharaj, Payal D.; Fang, Ying; Garcia, Sandra; Barker, Christopher M.; Smith, Kirk; Godsey, Marvin S.; Savage, Harry M.; Barton, Vonnita; Bolling, Bethany G.; et al. (PLOS Neglected Tropical Diseases, 2020)
Author summary Following the detection of West Nile virus in the United States, evidence of the historically endemic and closely related virus, St. Louis encephalitis virus (SLEV), dropped nationwide. However, in 2015, a novel genotype of SLEV, previously restricted to Argentina, was identified as the etiological agent of an outbreak of neurological disease in Arizona, United States. Since that time, the genotype has expanded throughout the Western United States, including into California, Nevada, Texas, Idaho, and Oregon. In this study, samples containing SLEV, provided by public health and mosquito abatement agencies, were sequenced and used in phylogenetic analyses to infer patterns of SLEV movement. Three independent routes of SLEV dispersal were identified: Arizona to Southern California, Arizona to Central California, and Arizona to all locations east of the Sierra Nevada mountains. The Sierra Nevada mountains and the Transverse Ranges appear to separate the three routes of SLEV movement, suggesting that geographic features may act as barriers to virus dispersal. Identification of patterns of SLEV dispersal can support regional public health agencies in improving vector mitigation efforts to protect their communities more effectively.